Profit strategies for air transportation - Radnoti, George (McGraw-Hill, 2002)
The book Presents practical and profitable solutions to problems encountered by commercial and regional airlines, charter, cargo, and corporate aircraft operations, businesses, and fractional and lease aircraft companies: Details save-money, make-money strategies and simulates trips for profit-and-loss analysis; Includes performance case studies; Covers methods of fuel conservation, environmental concerns, maintenance, and more.